2022
DOI: 10.3390/ani12192719
|View full text |Cite
|
Sign up to set email alerts
|

Clostridium butyricum and Its Culture Supernatant Alleviate the Escherichia coli-Induced Endometritis in Mice

Abstract: Endometritis is a disease with a high incidence in dairy cows and causes great economic loss to milk production. This study examined the therapeutic effects of Clostridium butyricum and its culture supernatant on Escherichia coli-induced endometritis in mice. The results showed that Clostridium butyricum and its culture supernatant effectively suppressed inflammatory responses of uterine tissues, such as uterine morphological changes, pathological damage, and the production of inflammatory cytokines. Clostridi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…Clostridium butyricum (ATCC 19398) showed anti-inflammatory effects in mice with endometritis when administered directly into the uterine tissues, resulting in an improvement in the birth rate of mice ( Mun et al, 2022 ). In this in vivo study, we observed anti-inflammatory effects in the uterine tissues, even though CBM 588 was orally administered to mice with endometritis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Clostridium butyricum (ATCC 19398) showed anti-inflammatory effects in mice with endometritis when administered directly into the uterine tissues, resulting in an improvement in the birth rate of mice ( Mun et al, 2022 ). In this in vivo study, we observed anti-inflammatory effects in the uterine tissues, even though CBM 588 was orally administered to mice with endometritis.…”
Section: Discussionmentioning
confidence: 99%
“…Clostridium butyricum (ATCC 19398), a butyrate-producing gram-positive anaerobe, shows anti-inflammatory effects against endometritis when administered directly into the uterus ( Mun et al, 2022 ). However, current probiotic dosing directly into the uterus is not realistic owing to technical issues in clinical situations, and the effects of orally administered C. butyricum on endometritis remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that isomalto-oligosaccharides had the strongest fermentability in both strains; however, SCFA production differed between the two strains ( Wang et al , 2014 ). Furthermore, the dietary probiotic C. butyricum could be found within the mucus layer, which was suggested to contribute to its action within the gut ( Xu et al , 2021a ; Mun et al , 2022 ). SCFAs, especially butyric acid, are produced by C. butyricum within the intestinal mucosa; therefore, these substances are easily accessible to hosts ( Molnár et al , 2020 ; Xu et al , 2021a ).…”
Section: Butyricum Interacts With Gut Microbes Toregulate Intestinal ...mentioning
confidence: 99%
“…Research has indicated that CB can improve the gut microenvironment, reduce the incidence of liver in ammation and enhance intestinal immunity by regulating liver and immune genes (Yamamoto et al 2022). Not only can CB improve the in ammatory microenvironment at the genetic level, but it can also enhance liver function by impacting liver metabolism (Mun et al 2022;Mencarelli et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Research has indicated that CB can improve the gut microenvironment, reduce the incidence of liver in ammation and enhance intestinal immunity by regulating liver and immune genes (Yamamoto et al 2022). Not only can CB improve the in ammatory microenvironment at the genetic level, but it can also enhance liver function by impacting liver metabolism (Mun et al 2022;Mencarelli et al 2013).Furthermore, CB also enhances the antioxidant function in animals. When added to the diet of hybrid groupers, it was found to improve growth performance, antioxidant capacity, and increase the abundance and diversity of bene cial gut bacteria (Yang et al 2023).…”
mentioning
confidence: 99%